2016
DOI: 10.1002/hed.24526
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy and transoral surgery as a definitive treatment for oropharyngeal cancer: A feasible novel approach

Abstract: Adjuvant chemotherapy followed by TOS and neck dissection is a feasible and efficacious novel therapeutic approach for definitive management of moderately advanced oropharyngeal cancer, reserving radiotherapy (RT) for salvage or adverse features. © 2016 Wiley Periodicals, Inc. Head Neck 38: 1837-1846, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 38 publications
(77 reference statements)
1
29
1
Order By: Relevance
“…4 Most trials have defined de-escalation following surgery as either reducing the dose of adjuvant radiation therapy or entirely omitting chemotherapy from adjuvant or definitive treatment. 9 Computed tomography (CT) and/or magnetic resonance imaging (MRI) of the neck was used prior to induction chemotherapy and postchemotherapy prior to surgical resection. 8 Distant-only metastatic recurrence accounts for almost 50% of all failures and remains a challenge that is not addressed with the current standard of treatment or other de-escalation trials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Most trials have defined de-escalation following surgery as either reducing the dose of adjuvant radiation therapy or entirely omitting chemotherapy from adjuvant or definitive treatment. 9 Computed tomography (CT) and/or magnetic resonance imaging (MRI) of the neck was used prior to induction chemotherapy and postchemotherapy prior to surgical resection. 8 Distant-only metastatic recurrence accounts for almost 50% of all failures and remains a challenge that is not addressed with the current standard of treatment or other de-escalation trials.…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of the approach is previously reported. 9 Computed tomography (CT) and/or magnetic resonance imaging (MRI) of the neck was used prior to induction chemotherapy and postchemotherapy prior to surgical resection. Previous studies have shown that, although there is a risk of false-positive results, FDGpositron emission tomography (PET) can potentially be similar in effectiveness in predicting tumor volume reduction when compared to endoscopic examination under general anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…The value contributed by the addition of 5‐FU into an induction chemotherapy regimen is controversial. Although most induction trials have used TPF triple therapy, a small set of articles have been published using TP‐based induction chemotherapy . These articles show similar efficacy and substantially lower toxicity profiles, therefore improving the viability and adherence to induction protocols.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this trial and other de-escalation trials will determine if treatment reduction is appropriate in patients with HPV-positive oropharyngeal cancers. Sadeghi et al (43) reported use of TORS after induction chemotherapy without any RT in 17 patients; this treatment failed in only one patient.…”
Section: Surgerymentioning
confidence: 99%